2019
DOI: 10.1037/str0000085
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear relationship between daily time pressure and work engagement: The role of psychological capital and sleep.

Abstract: The present study focuses on the fluctuation in work engagement by examining the relationship between daily time pressure and daily work engagement. Based on the job demands-resources (JD-R) theory, this study also tests whether psychological capital and sleep moderate the influence of time pressure on work engagement. We conducted a diary study to gather 67 participants' data over 10 consecutive work days (502 daily measurement points), including their daily time pressure, work engagement, and sleep quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 49 publications
(74 reference statements)
3
41
1
Order By: Relevance
“…Research regarding the role psychological resources play in leaders' effectiveness has mostly focused on psychological capital, found to alleviate the strain caused by high job demands (Hur et al, 2016;Sheng et al, 2019) and, alongside other positive resources such as mindfulness, to predict the well-being of leaders (Roche et al, 2014). When leaders' psychological capital is high, the quality of leader-member exchange increases, in turn promoting high psychological capital for followers (Chen et al, 2019).…”
Section: Leader Psychological Resources and Leader Effectivenessmentioning
confidence: 99%
“…Research regarding the role psychological resources play in leaders' effectiveness has mostly focused on psychological capital, found to alleviate the strain caused by high job demands (Hur et al, 2016;Sheng et al, 2019) and, alongside other positive resources such as mindfulness, to predict the well-being of leaders (Roche et al, 2014). When leaders' psychological capital is high, the quality of leader-member exchange increases, in turn promoting high psychological capital for followers (Chen et al, 2019).…”
Section: Leader Psychological Resources and Leader Effectivenessmentioning
confidence: 99%
“…al., 2007). Work engagement is related to employees' sense of well-being, a perfect state that allows them to experience positive emotions while at their workplace (Sheng et al, 2017). As a factor promoting employees' well-being, work engagement will be achieved if employees have adequate psychological resources, which will reduce the negative pressures of high job demands (Schaufeli, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is a capacity to rebound from failure, whereas optimism is a positive attribution of current and future conditions (Luthans & Youssef-Morgan, 2017). Previous research by Sheng et al (2017) identified psychological capital as a psychological resource that has a significant impact on work engagement, and other studies have supported this conclusion with findings that high levels of psychological capital among employees engenders a more positive job performance. On the other hand, low levels of psychological capital will contribute to a negative job performance (Avey, Reichard, Luthans & Mhatre, 2011).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, self-efficacy and optimism as important dimensions of psychological capital can significantly positively predict work input (Halbesleben, 2010 ; Wang et al, 2017 ). Other researchers have found that psychological capital not only has a direct positive predictive effect on work input but also can alleviate the negative impact of work requirements on work input (Sheng et al, 2019 ). In addition, a large number of studies have found that psychological capital can significantly and positively predict job involvement (Wang and Luo, 2015 ; Cheng and Gao, 2019 ; Mao et al, 2019 ; Wang J. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%